Influence of different biomass ash additive on anthracite pyrolysis process and char gasification reactivity - Xiaoming Li (International Journal of Coal Science & Technology, 2020)
Abstract Catalytic coal gasification technology shows prominent advantages in enhancing coal gasification reactivity and is restrained by the cost of catalyst. Two typical biomass ash additions, corn stalk ash (CSA, high K–Na and low Si) and poplar sawdust ash (PSA, high K–Ca and high Si), were employed to study the influence of biomass ash on pyrolysis process and char gasification reactivity of the typical anthracite. Microstructure characteristics of the char samples were examined by X-ray diffraction (XRD). Based on isothermal char-CO2 gasification experiments, the influence of biomass ash on reactivity of anthracite char was determined using thermogravimetric analyzer. Furthermore, structural parameters were correlated with different reactivity parameters to illustrate the crucial factor on the gasification reactivity varied with char reaction stages. The results indicate that both CSA and PSA additives hinder the growth of adjacent basic structural units in a vertical direction of the carbon structure, and then slow down the graphitization process of the anthracite during pyrolysis. The inhibition effect is more prominent with the increasing of biomass ash. In addition, the gasification reactivity of anthracite char is significantly promoted, which could be mainly attributed to the abundant active AAEM (especially K and Na) contents of biomass ash and a lower graphitization degree of mixed chars. Higher K and Na contents illustrate that the CSA has more remarkable promotion effect on char gasification reactivity than PSA, in accordance with the inhibition effect on the order degree of anthracite char. The stacking layer number could reasonably act as a rough indicator for evaluating the gasification reactivity of the char samples.